Instrumental popular music and students' reading comprehension: Basis for proposed reading remediation program - Ana Marie C. Diaz; Jasmin S. Villanueva (Northern Negros State College of Science and Technology (NONESCOST), 2022)
The potential of music to aid reading performance has been the subject of research for many years. The present study aimed to investigate the effect of five music genres (Jazz, Pop, RNB, Rap, and Classical) on the reading comprehension of grade 9 junior high school students in the division of Angeles City. In line with this, the study conducted quasi-experimental pretest and posttest for students (N=40) within the span of 2 weeks. The pretest of each genre was taken without playing popular instrumental music in the background while the posttest was taken while the subjects listened to popular instrumental music. Outcomes of the pretest indicate that students reading comprehension scores obtained a mean that ranged from 5.450 to 5.825. These results barely made the cut to the instructional reading comprehension level that, according to the Philippine Informal Reading Inventory (PHIL IRI) scale ranges from 5 to 7 points, in a ten-item test indicating a need for reading remediation. Results of the study showed a highly significant difference between pretest and post-test scores for the genres of Jazz Pop and Classical where all three genres obtained a p-value of 0.000 which was lower than the set alpha of 0.01 level of significance. Hence, a reading remediation program utilizing Jazz, Pop, and Classical music as a reading supplement has the potential to aid struggling readers. Therefore, based on the outcomes of this study, the researcher designed a proposed reading remediation program utilizing the three genres (Jazz, Pop, and Classical).